Vpliv lesne vrste na hrapavost zunanjega sloja in prostorninsko maso brušenih ivernih plošč - Medved, Sergej (Les (Ljubljana), 1999)
On the example of spruce (Picea abies Karst.), beech (Fagus silvatica L.), oak(Quercus robur L.) and poplar (Populus nigra L.) influence of wood species on surface roughness of sanded particleboards had been discoussed. Samples were sanded with sanding belt grid size 100 until reached the point of maximumdensity. For describing the influence of surface roughness, parameters Ra, Rz and Rmax were used. The lowest surface roughness was found in the boards whose surface was consisted of oak and poplar particles, the maximum surface roughness was found in the board whose surface layer was consisted of beech particles. Surface roughness was changed the most when we used particlesfrom oak and the least when we used particles from spruce. After sanding surface roughness decreased with increased density
Keywords: iverne plošče; les; brušenje; hrapavost